Tinjauan Hukum Warisan Perspektif Islam; Konsep Waris Dalam Al Quran, Al Sunnah Dan Kaidah Fikih - Herfin Fahri (Al Hikmah: Jurnal Studi Keislaman, 2023)
Inheritance is the process of transferring assets owned by someone who has died to the recipient (wara>thah) in which the number and size of the portion (nas}i>b) received has been determined in a will mechanism, or if there is no will, then the recipient party determines the number and size of its parts (haz{z{) are determined in the inheritance mechanism. The main priority in this matter lies in the will, that is, sometimes the heir has determined the will before he dies with all his wealth to his close relatives after he dies, this is based on the text of Allah that requires or the enactment of inheritance laws occurs after the will is carried out and the debt is paid. Sometimes he does not write any will, so Allah takes over this distribution by including it in the inheritance law mechanism and determines all parties receiving the inheritance as well as the share of the assets each of them receives. From this it is very necessary to review the law of inheritance to be studied and analyzed so that it will be more understandable and wise to take attitudes and decisions based on Islamic teachings, namely the concept of inheritance law based on the texts of the Quraâ€™an, al Sunnah, al Ijm>a', ijtihad al-s}ah}a>bah and fiqh rules. And the importance of studying the science of fara>id} is very important in the teachings of Islam as in the hadith narrated by Ibn Majah confirms "learn the science of faraidh and teach it, because it is half knowledge. the science of fara>id} will be forgotten. the science of fara>id} is the first thing that will be taken away from my ummah.â€ the science of fara>id} is half of science, because this knowledge is related to human life and is related to the concept of maqa>s}id al-shari>ah, one of which is guarding wealth (h}ifz}u al-ma>l). Keywords: inheritance law, inheritance concept, Islamic perspective